Benthic metrics as indicators of human disturbance in a marine-dominated lagoon - Jones, Amy M (Department of Biological Sciences, 2019)
Expanding anthropogenic developments along with the added stress of climate change, are negatively influencing coastal ecosystems. Because of their many benefits to mankind, it is important to identify key bioindicators that can detect disturbance-induced ecosystem change. Benthic metrics are an excellent example of disturbance indicators in soft sediment based aquatic systems, and are directly applicable to one of South Africa’s most economically and ecologically significant marine-dominated lagoons; Langebaan lagoon. This lagoon is managed through the designation of three zones (A, B and C) with contrasting human presence. Public access, recreation and bait-collecting is permitted in A, but no bait colleting is permitted in B. Human presence is completely restricted in Zone C. This study thus aimed to test the level of impact of human disturbance on two zones of the lagoon (A and C), using benthic metrics as bioindicators. Macrofaunal community metrics (abundance, species richness, Shannon-Weiner diversity, evenness, and community structure), performance of a key ecosystem engineer (sandprawn abundance and condition factor), organic matter content and microphytobenthic biomass were compared between the two sites, comprising multiple subsites. Results showed minimal differences between disturbed and undisturbed sites, with the exception of organic matter content and Shannon-Weiner diversity comparisons, which were greater in undisturbed subsites. There was however, a general trend of increasing dominance by sandprawns (Callichirus kraussi) from undisturbed to disturbed subsites, whilst the undisturbed subsites were numerically dominated by a several codominant polychaetes (Euclymene spp., Notomastus latericeus and Marphysa sanguinea). Interestingly, there were more significant differences at the subsite level, suggesting that localized conditions are more important in shaping macrobenthic communities than disturbance impacts, as supported by previous literature. Despite limitations, this study does provide important baseline data relevant to optimizing sampling designs for detecting human disturbance impacts in Langebaan Lagoon. Key Words: Benthic metrics, bioindicator, macrobenthos, disturbance, trampling, coastal lagoon.